85 Effect of a commercial phytogenic product on milk production. (7th December 2018) - Miller, B; Mendoza, S; Gaudin, F; Meyer, A
Abstract: With increased interest in reducing antibiotic use in animal agriculture there has been an increased interest in the use of phytogenic products. Within ruminant nutrition there have been products tested that are designed to modify rumen fermentation and products designed to promote gut health through anti-inflammatory and antioxidant activity. A field trial was conducted using a phytogenic product, Digestarom ® Dairy (BIOMIN Holding GmbH, Austria), to measure influence on energy corrected milk production. A commercial herd (Kenyon, MN) using a robot milking system was used for the test. Holstein cows, both prima and multi-parous were divided into two robot equipped pens each containing 62 cows (124 in total). Both groups of cattle averaged 45.0 kg in daily milk production Cattle were fed in a "switch back design" for four (4) weeks with a two week "rest period" were no treatment was supplied. Treatment consisted Digestarom ® Dairy incorporated in the "robot" feed pellet in one group at a rate of 2 g per 5.7 kg of fed (0.035%) vs. control, the same pellet but without the phytogenic additive. All cows received the same partial mixed diet which included all feed not provided in the robot feeder. An automatic "broom" pushed feed up several times per day to assure that cattle always had access to this part of the diet. This was a commercial herd there were cows entering and leaving the groups, freshening and dry off. Only cows, total of 118, that went through the entire protocol were used in the statistical analysis. Data was analyzed with the GLIMMMIX procedure of SAS (Cary, NC). Results are presented in the table below. Feeding Digestarom® Dairy in this herd significantly improved energy corrected milk production.